2019
DOI: 10.1063/1.5096850
|View full text |Cite
|
Sign up to set email alerts
|

Linear theory of multibeam parametric instabilities in homogeneous plasmas

Abstract: Linear theory of parametric instabilities resulting from N overlapping laser beams with an arbitrary beam configuration and polarization in a homogeneous plasma is presented. A general dispersion relation valid for both N-beam stimulated Raman scattering (SRS) and stimulated Brillouin scattering (SBS) is derived. Analytically, we obtain the growth rate for a two-beam system and find the significance of two special geometries by sharing a common decay wave. By virtue of these geometries, the coefficient matrix … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 36 publications
0
19
0
Order By: Relevance
“…For more than three beams, a common plasma wave exists only when the intersection points between the three spheres formed by k sα (α = 1, 2, 3) happen to be located on spheres formed by other k sα (α = 4, • • • ). This imposes a stringent requirement on the beam symmetry as noticed by [14]. For an indirect drive, the required beam symmetry can be satisfied only in a quite limited volume near the laser entrance hole (LEH), when the incident laser beams are angularly distributed in a highly symmetric configuration [1].…”
Section: Theoretical Model For Sp Modes Of Two Beams a Matching Geome...mentioning
confidence: 99%
See 1 more Smart Citation
“…For more than three beams, a common plasma wave exists only when the intersection points between the three spheres formed by k sα (α = 1, 2, 3) happen to be located on spheres formed by other k sα (α = 4, • • • ). This imposes a stringent requirement on the beam symmetry as noticed by [14]. For an indirect drive, the required beam symmetry can be satisfied only in a quite limited volume near the laser entrance hole (LEH), when the incident laser beams are angularly distributed in a highly symmetric configuration [1].…”
Section: Theoretical Model For Sp Modes Of Two Beams a Matching Geome...mentioning
confidence: 99%
“…The shared daughter wave can be a common Langmuir/ion acoustic wave or scattered light wave, termed as the shared plasma wave (SP) mode and shared scattered light wave (SL) mode, respectively. Theoretically, the homogeneous temporal growth rate for collective SP and SL modes of multiple beams has been investigated in a general framework under fluid description [13][14][15]. However, for most practical cases in ICF, SRS and SBS instabilities are spatial problems [16][17][18][19], for which theoretical work for the collective modes is lacking.…”
Section: Introductionmentioning
confidence: 99%
“…Significant progresses in LPI studies have been achieved during recent decades [9][10][11] , but there are still many LPI problems remaining unclarified. Among them, nonlinearities [12] are the most important and highlighted, since nonlinear processes govern the saturation of LPIs (which decide the final energy loss from LPIs) in ICF experiments.…”
Section: Introductionmentioning
confidence: 99%
“…Langmuir wave is one of the eigen-modes in plasma whose the frequency is close to the plasma frequency, 1,2 and thus in inertial confinement fusion (ICF) [3][4][5] an incident pump laser can easily decay to a reflected electromagnetic wave and a Langmuir wave, which is the so-called stimulated Raman scattering (SRS). [6][7][8][9][10][11][12][13] Because this instability consumes pump energy and produces hot electrons, which are detrimental to fusion, it is crucial to find the saturation mechanism of SRS. [14][15][16][17] At 1960s, Kruer et al revealed a trapped-particle instability that Langmuir wave can decay to sidebands, 18 , and it can serve as a saturation mechanism of SRS.…”
Section: Introductionmentioning
confidence: 99%